The effect of special exercises on some physiological variables and endurance of skill performance in basketball (Damu Journal of Sport Sciences, 2024)
Some physiological variables associated with basketball players' health were assessed through the training curriculum, including systolic blood pressure, diastolic blood pressure, heart rate, breathing times, glucose levels, hemoglobin, hemoglobin, red blood cells, and white blood cells.Basketball players' body weight, upper arm fat, Plate, and abdominal fat are all factors that a training approach can affect.Through the results of this study, it was concluded that there is a positive effect of the training curriculum on the percentage of fat (upper arm, buttocks, and abdomen), weight in kilograms, sugar percentage, and number of white blood cells, as the differences between the pre-school stage and the school period.The post-measurements were statistically significant and in favor of the post-measurement of these variables.There is a negative effect of the training curriculum on the hemoglobin percentage, the hematocrit percentage, and the number of red blood cells, as the differences between the pre- and post-measurements were statistically significant and in favor of the pre-measurement. Of these variables, there is no effect of the training curriculum on systolic and diastolic blood pressure, heart rate, and number of breathing times, and there are no statistically significant differences between the pre- and post-measurements of these variables.As for the second and third conclusions, the researcher attributed this approach directly to the application of the training curriculum